2010
DOI: 10.1177/1087054710368486
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Treatment of ADHD With Stimulants

Abstract: The study findings underscored the diversity of ADHD patients and that individual factors should be taken into account when tailoring individual treatment schedules. Findings further showed that stimulant dosages are dynamic over time and depend on individual factors, that individual factors influence outcome, and that patients with ADHD should be individually monitored and stimulant dosages adjusted continuously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…The mechanisms lying at the root of the increased effect on weight in subjects with ASD remain to be investigated. In a previous paper [ 35 ], we found that autistic subjects did not differ from the other patients regarding CS dosage which rules out dosing differences as an explanation. Their weight z-scores attenuated earlier, and at 72+ months their weight z-scores reached a level significantly above normative data, and CS dosage therefore had almost no long-term impact on weight.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…The mechanisms lying at the root of the increased effect on weight in subjects with ASD remain to be investigated. In a previous paper [ 35 ], we found that autistic subjects did not differ from the other patients regarding CS dosage which rules out dosing differences as an explanation. Their weight z-scores attenuated earlier, and at 72+ months their weight z-scores reached a level significantly above normative data, and CS dosage therefore had almost no long-term impact on weight.…”
Section: Discussionmentioning
confidence: 58%
“…We expected that CS treatment from an early age would have a larger impact on growth parameters than treatment start at an older age; but, in fact, we saw the opposite. This finding could not be explained by a more cautious titration of dosage among these young starters as they were treated with high dosages [ 35 ]. This contrasts with the literature documenting greater susceptibility to adverse effects among preschool children [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies indicate that comorbid anxiety disorders are associated with a lower effect of medication on ADHD symptoms and psychosocial functioning, which leads to discontinuation of medical treatment [ 30 ]. A study of children and adolescents documented that, among treated individuals, about 6% were also treated for emotional disorders [ 77 ]. Some clinical samples of adolescents with ADHD have reported even higher levels of emotional problems [ 78 ].…”
Section: Discussionmentioning
confidence: 99%